Kulturna kompetentnost v slovenski bolnišnični prehrani - Halbwachs, Helena Kristina (Obzornik zdravstvene nege, 2022)
Introduction: Adherence to dietary restrictions and principles related to the cultural background of patients is important in hospital nutrition, as nutrition has an impact on health outcomes, as well as on the length and cost of hospitalisation. This approach requires organisational and individual cultural competence. The purpose of the study was to explore the perspective of those responsible for hospital nutrition on cultural competence, assess whether hospital nutrition is adapted to patients' cultural background and identify the challenges in this area. Methods: A qualitative research using semi-structured interviews was conducted. We interviewed 14 food service managers and nutritionists from eight Slovenian hospitals. The data were analysed using a deductive content analysis within Atlas.ti software. Results: The respondents were aware of the diversity of the patients and the importance of adapting the diet to the cultural background, although the concept of cultural competence is unfamiliar. There are limitations in adapting diets. Knowledge on cultural aspects of nutrition is scarce and training in this area is almost unavailable. Other challenges such as organisational, technological and communication challenges hinder the development of cultural competence. Discussion and conclusion: Similar challenges to ours are also faced abroad. Although, according to the respondents, patients have many possibilities to adapt their diet, it would be difficult to claim that cultural competence exists, as this concept encompasses other skills as well. Further research, educational opportunities on the cultural aspects of nutrition and awareness of the importance of nutritional services at all levels in the healthcare system are needed to further develop cultural competence in this area.
Keywords: bolnišnice; kulturni vidik prehrane; prehrana; raznolikost; razvoj